The role of health promotional leadership for employee health and work engagement in South Africa - Glenny, Bernice (Organisational Psychology, 2025)
Poor employee health and work disengagement have costly repercussions for organisations. To understand better how employers could support employee health, the study presented in this dissertation tested if employee's direct supervisors could do so when they show health promotional leadership behaviours. Additionally, it explored if such behaviours might also increase work engagement via physical and psychological wellbeing as mediator variables. The study employed a descriptive, quantitative survey design. Employees who reported to a leader in South Africa (N = 169) completed an online questionnaire which measured how they perceived their leader's role in health promotion and their own levels of work engagement and wellbeing. Linear regression analysis supported the hypotheses: Greater health promoting leadership was related to greater employee work engagement and this relationship was mediated by wellbeing. This suggests that leaders should take note of the importance of those leadership behaviours which promote employee's health and that it might be beneficial to train leaders to show these behaviours. The study findings suggest that health promoting leadership might not only benefit employees, but also the employing organisation due to its link with greater work engagement via greater mental and physical health. Further research should test this assumption as the study's descriptive design merely shows that the variables of interest are related, but not which one causes the other.